Dampak Social Influence, Digital Literacy, dan Political Issues Terhadap Keputusan Pembelian Cryptocurrency di Indonesia (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study investigates the impact of social influence, digital literacy, and political issues on cryptocurrency purchase decisions in Indonesia, using the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical framework. Data from 101 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that only social influence has a statistically significant effect on cryptocurrency purchase decisions, while digital literacy and political issues do not. All constructs demonstrated acceptable levels of validity and reliability. These results offer valuable insights into Indonesian consumer behavior in adopting digital assets, and provide practical implications for policymakers and fintech industry stakeholders.